Tumor marker detection using surface enhanced Raman spectroscopy on 3D Au butterfly wings. Issue 8 (3rd February 2017) - Song, Guofen; Zhou, Han; Gu, Jiajun; Liu, Qinglei; Zhang, Wang; Su, Huilan; Su, Yishi; Yao, Qinghua; Zhang, Di
Abstract : Tumor markers are usually over-expressed in human body fluids during the development of cancers. Abstract : Tumor markers are usually over-expressed in human body fluids during the development of cancers. Monitoring tumor markers' level is thus important for early diagnosis and screening of cancers. One way to achieve this is based on the surface enhanced Raman scattering (SERS) technique that can drastically amplify Raman signals of analytes on a plasmonic metal ( e.g., Au, Ag, and Cu) surface. However, this promising method suffers from aggregation of plasmonic nanoparticles. Here we report a stable, reproducible, and facile SERS-based readout method to detect an important tumor marker, carcinoembryonic antigen (CEA). This route utilizes Au butterfly wings with natural three dimensional (3D) hierarchical sub-micrometer structures rather than relying on the aggregates of metal nanoparticles. The Au butterfly wings show excellent SERS property and are temperature (80 °C) and time (6 months) stable on a sub-micrometer scale. Thus, the detecting antibodies and enzyme-linked secondary antibodies that are usually applied in conventional enzyme-linked immunosorbent assay (ELISA) can be replaced by chemically synthesized CEA aptamers, significantly simplifying the whole detection process. We demonstrate the feasibility of this method via quantitative detection of clinical CEA level in human body fluids. This work thus demonstrates a promising tumor marker detection technique based on a hierarchical sub-micrometer SERS structure, which could be useful for the mass screening of early stage cancers.